Meningkatkan Employee Sustainability melalui Job Involvement dan Work-Life Reconciliation pada Pegawai Sektor Publik - Irman A.D.; Muhammad Aqil; Nur Wahyunianti Dahri; M Said Abdullah (Pascasarjana Universitas Muhammadiyah Mamuju, 2026)
This study aims to analyze the effect of job involvement and reconciliation on sustainable employee among employees of the Sampaga Subdistrict Office in West Sulawesi Province. This research used a quantitative approach with a survey method. The population consisted of all employees of the Sampaga Subdistrict Office, and a census sampling technique was applied because of the relatively small number of respondents. Data were collected through closed-ended questionnaires using a Likert scale and analyzed using multiple linear regression. The results show that job involvement has a significant partial effect on sustainable employee. Reconciliation also has a significant partial effect on sustainable employee. Simultaneously, job involvement and reconciliation were proven to have a significant effect on sustainable employee. The novelty of this research lies in the integration of the work relationship reconciliation concept as a key factor in maintaining employeesustainability in the public sector, which often faces unique bureaucratic pressures and interpersonal conflicts.These findings indicate that employee involvement in work and the ability to rebuild harmonious relationships are important factors in creating productive, adaptive, and sustainable employees within the organization. Therefore, organizations need to pay attention to strengthening job involvement and maintaining good interpersonal relationships so that employee sustainability can be preserved in the long term.